Understanding families a global introduction - McKie, Linda; Callan, Samantha; Sage eBooks (London : SAGE, 2012)
A student-orientated textbook which introduces the main concepts, theories and research methods needed to study the family, this text explains how modern families can be explored and understood in research, policy and practice.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Families; Families -- Psychological aspects; Electronic books